Structure-Activity Relationships of Cationic Lipidoids against Escherichia coli - James Jennings; Dunja Ašćerić; Nermina Malanovic; Georg Pabst (MDPI AG, 2023)
Membrane-active molecules provide a promising strategy to target and kill pathogenic bacteria. Understanding how specific molecular features drive interactions with membrane components and subsequently cause disruption that leads to antimicrobial activity is a crucial step in designing next-generation treatments. Here, we test a library of lipid-like compounds (lipidoids) against Gram-negative bacteria Escherichia coli to garner in-depth structure-activity relationships using antimicrobial assays. Modular lipidoid molecules were synthesized in high-throughput, such that we could analyze 104 compounds with variable combinations of hydrophobic tails and cationic headgroups. Antibacterial activity was strongly correlated to specific structural features, including tail hydrophobicity and headgroup charge density, and also to the overall molecular shape and propensity for self-assembly into curved liquid crystalline phases. Dye permeabilization assays showed that E. coli membranes were permeabilized by lipidoids, confirming their membrane-active nature. The reduced permeabilization, as compared to Gram-positive Bacillus subtilis, alludes to the challenge of permeabilizing the additional outer membrane layer of E. coli. The effect of headgroup solubility in gemini-type lipidoids was also demonstrated, revealing that a headgroup with a more hydrophilic spacer between amine groups had enhanced activity against B. subtilis but not E. coli. This provides insight into features enabling outer membrane penetration and governing selectivity between bacterial species.